Potential problems and concepts of utilizing haji dormitories equivalent to star hotels to improve the national economy - I Ketut Sirna; Gusti Ngurah Joko Adinegara; I Wayan Damayana (Journal of Applied Sciences in Travel and Hospitality, 2024)
The research was conducted at the Surabaya Embarkation Haji Dormitory with the aim of: mapping potential problems, namely: products, services, management and relevant policies, towards the concept of using Haji dormitories on a par with star hotels to improve the national economy. Problems studied: (1) How to map the potential problem of Haji dormitories equivalent to star hotels to improve the national economy?, (2) What is the concept of using Haji dormitories equivalent to star hotels to improve the national economy? This re-search uses descriptive, qualitative, quantitative methods, star hotel assessment study approaches, as well as community base tourism. Data is analyzed using the theory of hotel and tourism quality standards, and rele-vant theories according to the data found at the research site. Research stages: will produce mapping poten-tial issues and concepts for utilizing Haji dormitories equivalent to star hotels, and strategic policies by formu-lating quality management standards. The results of this research analysis are: Surabaya Haji embarkation dormitories do not meet standards equivalent to star hotels, because there are still many star hotel standard items that have not been met, and if you look at the standard score of a three star hotel between 600-700, and the Surabaya Embarkation Haji Dormitory only meets the score of only 400, or 33.30% less than 100%, with a score range of 1 to 5 then the average score for the Haji dormitory is Surabaya embarkation only reached 3.7. Research is expected to support national economic development programs to increase national income outside of taxes.